EFFECTIVITY OF ONLINE SUMMONS OF THE PARTIES (E-SUMMONS) IN PADANGSIDIMPUAN STATE COURT - Wiwik Tinasari (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2022)
Supreme Court Regulation Number 1 of 2019 Concerning Electronic Administration of Cases and Trials in Courts is an expansion and refinement of the previous regulation, namely Perma Number 3 of 2018. This regulation gives authority to bailiffs/substitute bailiffs at court to submit relaas (summons/ notifications) online, so that justice seekers are expected to no longer have to wait for the usual trial time. The research method used is descriptive qualitative research method with the type of empirical legal research. The results of this study indicate that summoning the parties online (E-Summons) and the case administration service process at the Padangsidimpuan District Court have been able to provide a level of satisfaction from the segmentation of time efficiency and costs incurred by legal subjects.Keywords: Effectiveness, e-summons, parties